2019
DOI: 10.1108/et-10-2018-0216
|View full text |Cite
|
Sign up to set email alerts
|

The role of practical assessment in the delivery of successful enterprise education

Abstract: Purpose The purpose of this paper is to concentrate on how assessment is used to support the aims of enterprise education leading to recommendations for improvements to the current approach to the assessment of enterprise. Design/methodology/approach This paper presents a review of entrepreneurship education literature and a qualitative case study conducted on a sample of enterprise educators at University of the West of Scotland. Data were analysed using thematic analysis. Findings Paradoxically, the trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Its emergence may be attributed to the acknowledgement of the need to differentiate between business education and entrepreneurship/ enterprise; the latter being more concerned with motivating students towards a propensity for creativity and innovation (Turner and Mulholland, 2017). Hytti and O'Gorman (2004) outline the distinction between entrepreneurship education and what they describe as 'traditional' management studies, although it is observed that there remains somewhat of a business school bias towards the promotion of business venturing (Fayolle et al, 2006;Herrmann, 2008;Murray, 2019) and this has resulted in some scholars questioning key tenets associated with traditional approaches to enterprise and entrepreneurship: '[ . .…”
Section: Enterprise Educationmentioning
confidence: 99%
“…Its emergence may be attributed to the acknowledgement of the need to differentiate between business education and entrepreneurship/ enterprise; the latter being more concerned with motivating students towards a propensity for creativity and innovation (Turner and Mulholland, 2017). Hytti and O'Gorman (2004) outline the distinction between entrepreneurship education and what they describe as 'traditional' management studies, although it is observed that there remains somewhat of a business school bias towards the promotion of business venturing (Fayolle et al, 2006;Herrmann, 2008;Murray, 2019) and this has resulted in some scholars questioning key tenets associated with traditional approaches to enterprise and entrepreneurship: '[ . .…”
Section: Enterprise Educationmentioning
confidence: 99%
“…The central goal of higher education centres on the growth and development of students more than the number who complete their degrees. The quality of education involves critical factors such as pedagogical instruction and the content of what is taught and learnt, with assessment playing a key role as a pillar to deep learning (Murray, 2019). The theoretical underpinnings of assessment in higher education focus attention on how to measure the quality of what is taught, what students learn and how to ascertain that learning has taken place.…”
Section: The Theory Of Assessment In Higher Educationmentioning
confidence: 99%
“…The concept of constructive alignment is based on a belief that diverse and larger classes create difficulty in maintaining academic standards, with an existing nexus between teaching and learning and assessment (Biggs, 1999;Murray, 2019). It is contended that when all components are aligned the students can achieve high order learning.…”
Section: Aligning Assessment With Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…(Inspired by Liñán et al, 2011;Marques et al, 2012;Eid et al, 2019) Throughout the course of this journey, the student is exposed to curricular and cocurricular interventions which are grounded in the principles of both practical and valuable entrepreneurial learning (see Murray, 2019b). If successful, the destination for the journey is employment for the graduate who is equipped with the range of competencies.…”
Section: Figure 2 Perception To Proclivity Process Modelmentioning
confidence: 99%